Astrocytic Control of Biosynthesis and Turnover of the Neurotransmitters Glutamate and GABA - Schousboe, Arne; Bak, Lasse K.; Waagepetersen, Helle S. (Frontiers in Endocrinology, 2013)
Glutamate and GABA are the quantitatively major neurotransmitters in the brain mediating excitatory and inhibitory signaling, respectively. These amino acids are metabolically interrelated and at the same time they are tightly coupled to the intermediary metabolism including energy homeostasis. Astrocytes play a pivotal role in the maintenance of the neurotransmitter pools of glutamate and GABA since only these cells express pyruvate carboxylase (PC), the enzyme required for de novo synthesis of the two amino acids. Such de novo synthesis is obligatory to compensate for catabolism of glutamate and GABA related to oxidative metabolism when the amino acids are used as energy substrates. This, in turn, is influenced by the extent to which the cycling of the amino acids between neurons and astrocytes may occur. This cycling is brought about by the glutamate/GABA – glutamine cycle the operation of which involves the enzymes glutamine synthetase (GS) and glutaminase (PAG) together with the plasma membrane transporters for glutamate, GABA and glutamine. The distribution of these proteins between neurons and astrocytes determines the efficacy of the cycle and it is of particular importance that GS is exclusively expressed in astrocytes. It should be kept in mind that the operation of the cycle is associated with movement of ammonia nitrogen between the two cell types and different mechanisms which can mediate this have been proposed. This review is intended to delineate the above mentioned processes and to discuss quantitatively their relative importance in the homeostatic mechanisms responsible for the maintenance of optimal conditions for the respective neurotransmission processes to operate.